2005
DOI: 10.1021/jp051645u
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Glutathione S-Transferase with Hypericin:  A Photophysical Study

Abstract: The photophysics of hypericin have been studied in its complex with two different isoforms, A1-1 and P1-1, of the protein glutathione S-transferase (GST). One molecule of hypericin binds to each of the two GST subunits. Comparisons are made with our previous results for the hypericin/human serum albumin complex (Photochem. Photobiol. 1999, 69, 633−645). Hypericin binds with high affinity to the GSTs: 0.65 μM for the A1-1 isoform and 0.51 μM for the P1-1 isoform (Biochemistry 2004, 43, 12761−12769). The photoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
(105 reference statements)
1
12
0
Order By: Relevance
“…The ability of LDL to solubilize hypericin is significant because hypericin has been reported to be most active in its monomeric form (35). )0.07 ± 0.01---)0.07 ± 0.01 10.3 ± 0.5 10.3 ± 0.5 LDL:Hyp = 1:10 § )0.06 ± 0.01-)0.02 ± 0.01 0.9 ± 0.2 )0.04 ± 0.01 10.3# 7.2 ± 1.2 LDL:Hyp = 1:30 § )0.06 ± 0.01-)0.03 ± 0.01 1.6 ± 0.3 )0.03 ± 0.01 10.3# 6.0 ± 1.0 HSA:Hyp = 1:1|| (13) 0.32 --0.32 31 31 GST (HA1-1 ⁄ HP1-1):Hyp = 1:1|| (14) 0.30 --0.30 ‡20 ‡20…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of LDL to solubilize hypericin is significant because hypericin has been reported to be most active in its monomeric form (35). )0.07 ± 0.01---)0.07 ± 0.01 10.3 ± 0.5 10.3 ± 0.5 LDL:Hyp = 1:10 § )0.06 ± 0.01-)0.02 ± 0.01 0.9 ± 0.2 )0.04 ± 0.01 10.3# 7.2 ± 1.2 LDL:Hyp = 1:30 § )0.06 ± 0.01-)0.03 ± 0.01 1.6 ± 0.3 )0.03 ± 0.01 10.3# 6.0 ± 1.0 HSA:Hyp = 1:1|| (13) 0.32 --0.32 31 31 GST (HA1-1 ⁄ HP1-1):Hyp = 1:1|| (14) 0.30 --0.30 ‡20 ‡20…”
Section: Discussionmentioning
confidence: 99%
“…In the biological context, we have extensively studied the interaction of hypericin with proteins such as human serum albumin (HSA) (13) and two different isoforms of glutathione S-transferase (GST), HA1-1 and HP1-1 (14). These studies reveal that hypericin forms a rigid complex with these proteins.…”
Section: Introductionmentioning
confidence: 99%
“…43 These beads can be used for encapsulation of bioactive agents like cells, enzymes, proteins and vaccines. 44 Recent studies have reported the preparation of poly(N-isopropylacrylamide) (PNIPAAm)/alginate gels as semi-interpenetrating polymer networks and comb-type graft hydrogels, based on the cation-mediated crosslinking of alginate with Ca 2+ ions. 45 -50 PNIPAAm is one of the most widely studied thermo-sensitive polymers, exhibiting a reversible temperature-sensitive phase transition in aqueous solutions at a lower critical solution temperature (LCST) of ca 32 • C. 51 Below this LCST, PNIPAAm is water-soluble and hydrophilic, existing in a coil conformation; above this LCST, PNIPAAm undergoes a sharp coil-to-globule transition, forming hydrophobic associations.…”
Section: Introductionmentioning
confidence: 99%
“…No significant swelling of microspheres occurred at this pH value together with insignificant BSA release because of the pH sensitivity of alginate. 4,5,11 Therefore, more proteins would be protected by microspheres from gastric juice when the protein-loaded microspheres were administrated by an oral route. Calcium ions have been reported to exchange with monovalent nongelling ions, mainly sodium and potassium ions, under physiological conditions.…”
Section: Effect Of the Release Medium On Bsa Release In Vitromentioning
confidence: 99%
“…The loading efficiency of water-soluble drugs, in particular, is much lower than that of water-insoluble drugs, and this is due to leakage of the drugs from alginate microspheres with large gel porosity. 11 The complex drug release mechanism from a swellable alginate matrix results in the uncontrolled and quick release of loaded drugs within a few minutes in simulated intestinal fluid (SIF). 8,10 In most cases, this method is employed to encapsulate micromolecular drugs that are insensitive to shear and heat because of the potential destructive effect of the air shear force.…”
Section: Introductionmentioning
confidence: 99%